Process stages energy efficiency increasing in high capacityammonia production plants (1360–1420tNH₃/day) - Tovazhnyanskyy, Leonid Leonidovich; Loboyko, O. Y.; Ved, V. E.; Arsenyeva, Olga Petrovna; Perevertaylenko, Oleksandr Yurievich (My University, 2019)
There are presented the results of low temperature CO to CO₂ conversion investigations for decreased steam consumption and deeper conversion of CO in nitrogen-hydrogen mixture. The results of monoethanolamine purification stage retrofit are presented too.
Keywords: ammonia plant; nitrogen-hydrogen mixture; conversion; carbon oxide; reaction; equilibrium; reaction rate; energy efficiency; steam